Comparative Viability of Francisella tularensis subsp. mediasiatica and subsp. holarctica under in vivo and in vitro Conditions - V. V. Evseeva; G. M. Titareva; I. V. Bakhteeva; T. B. Kravchenko; A. I. Borzilov; T. I. Kombarova; R. I. Mironova; N. Yu. Krasavina; G. Kh. Bazarova; E. N. Rozhdestvensky; V. S. Timofeev (Проблемы особо опасных инфекций, 2025)
The aim of the work was to compare the survival ability of virulent strains of tularemia microbe, mediasiatica and holarctica subspecies, endemic to Russia, in the aquatic environment and in the animal organism. Materials and methods. 11 virulent strains of various subspecies deposited in the State collection “SCPM-Obolensk” were used in the work. To assess the survival rate, bacterial cells of the studied strains at a concentration of 5·106 CFU/ml were incubated for 35 days in autoclaved tap water. The viability of Francisella tularensis bacterial cells was determined immediately before the experiment and then weekly by seeding on agar plates. To compare the holarctica and mediasiatica strains by in vivo survival ability during co-infection, the strain mixture was passaged three times through mice, the ratio of colonies of each strain in the spleen being calculated at each passage. Colony differentiation was performed by assessing the length of the Ft-M20 VNTR locus using PCR and subsequent gel electrophoresis. Results and discussion. Subsp. mediasiatica shows significantly lower ability to survive in water compared to subsp. holarctica. At the same time, analysis of the results of seeding after co-infection of mice with strains belonging to the two subspecies indicates that subsp. mediasiatica reproduces in the host organism more effectively than subsp. holarctica.